(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
This abstract explores the collaborative relationship between nurses and radiologists in the field of radiology and its impact on patient well-being. Radiology is a crucial aspect of modern healthcare, providing essential diagnostic and therapeutic services. Nurses and radiologists work closely together throughout the imaging process, from pre-procedural preparation to post-procedural care and follow-up. This collaboration ensures patient safety, comfort, and satisfaction during imaging procedures.